THE INTERNET AS A SITE OF LEGAL EDUCATION AND COLLABORATION ACROSS CONTINENTS AND TIME ZONES: USING ONLINE DISPUTE RESOLUTION AS A TOOL FOR STUDENT LEARNING - Simmons, Martha E.; Thompson, Darin (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
Increasingly, digital technologies are influencing and impacting dispute resolution, particularly in the emerging field of online dispute resolution (ODR). ODR holds the potential to increase access to justice by engaging disputants in dramatically new ways. As a relatively new subject, ODR is unlikely to form part of the traditional curriculum at law schools. Aside from the question of whether it will become a mainstream part of tomorrow’s legal or dispute resolution landscape, ODR does show us that a familiarity with technology is becoming more important for tomorrow’s lawyers. As educators, how can we expose law students to these new forces of change in a meaningful way? How can we help students understand the benefits and drawbacks technology holds for the challenge of access to justice? This article describes a unique pilot project of an ODR simulation involving three universities in three cities, two continents, and three time zones. The main objectives of the project were to expose law students to ODR from the perspective of a disputant or client; expose clinical mediation students to a range of technology-based dispute resolution processes; demonstrate the potential for technology to support collaboration across vast distances; and promote experiential education by giving students “hands-on” ODR experience. This article will describe the simulation from an educator’s perspective.